Behavioural and emotional problems, intellectual impairment and health‐related quality of life in patients with organic acidurias and urea cycle disorders. Issue 2 (27th August 2015) - Jamiolkowski, Dagmar; Kölker, Stefan; Glahn, Esther M.; Barić, Ivo; Zeman, Jiri; Baumgartner, Matthias R.; Mühlhausen, Chris; Garcia‐Cazorla, Angels; Gleich, Florian; Haege, Gisela; Burgard, Peter; ,
Abstract: Background: Organic acidurias (OADs) and urea cycle disorders (UCDs) are inborn metabolic disorders with a risk for acute and chronic metabolic decompensation resulting in impairments of the central nervous system and other organ systems. So far, there is no systematic study of intellectual functioning, behavioural/emotional problems and health‐related quality of life (HRQoL), and how these domains are connected. Methods: Data of 152 patients with OADs ( n = 100) and UCDs ( n = 52) from the European Registry and Network of intoxication type Metabolic Diseases (E‐IMD) using standardized instruments were compared with normative data. Results: Behavioural/emotional problems are increased in OADs or UCDs patients by a factor of 2.5 (3.0), in female asymptomatic carriers of X‐linked inherited UCD ornithine transcarbamylase deficiency (fasOTCD) by a factor of 1.5. All groups show similar patterns of behavioural/emotional problems, not different from epidemiological data. Mental disability (IQ ≤ 70) was found in 31 % of OAD, 43 % of UCD, but not in fasOTCD subjects. HRQoL was decreased in the physical domain, but in the normal range. Behavioural/emotional problems were significantly associated with intellectual functioning (OR = 6.24, 95 %CI: 1.39–27.99), but HRQoL was independent from both variables. Conclusions: Patients with OADs and UCDs show increased frequencies of mental disability and behavioural/emotional problems. Profiles of behavioural/emotional problems were similar to epidemiological data. Intellectual disability and behavioural/emotional problems were strongly associated. Patients' HRQoL was in the normal range, possibly compensated by coping strategies of their families. Diagnostics and clinical care of OAD/UCD patients should be improved regarding behavioural/emotional, intellectual and quality of life aspects.